Investigation of iron spin crossover pressure in Fe-bearing MgO using hybrid functional. (21st March 2018) - Cheng, Ya; Wang, Xianlong; Zhang, Jie; Yang, Kaishuai; Zhang, Chuanguo; Zeng, Zhi; Lin, Haiqin
Abstract: Pressure-induced spin crossover behaviors of Fe-bearing MgO were widely investigated by using an LDA  +   U functional for describing the strongly correlated Fe–O bonding. Moreover, the simulated spin crossover pressures depend on the applied U values, which are sensitive to environments and parameters. In this work, the spin crossover pressures of (Mg1− x, Fe x )O are investigated by using the hybrid functional with a uniform parameter. Our results indicate that the spin crossover pressures increase with increasing iron concentration. For example, the spin crossover pressure of (Mg0.03125, Fe0.96875 )O and FeO was 56 GPa and 127 GPa, respectively. The calculated crossover pressures agreed well with the experimental observations. Therefore, the hybrid functional should be an effective method for describing the pressure-induced spin crossover behaviors in transition metal oxides.